Penile duplication (diphallia) with epispadias, neurogenic bladder, and lumbar vertebral Fusion: An exceptionally rare multisystem congenital association - Narjes Saberi; Farid Rajaei Rizi; Mohammad Nozari (Urology Case Reports)
We report a highly unusual case of penile duplication (diphallia) accompanied by epispadias, neurogenic bladder with markedly reduced compliance, and lumbar vertebral fusion. Comprehensive clinical, imaging, and urodynamic examinations delineated complex genitourinary and spinal anomalies necessitating multidisciplinary management. The discussion reviews embryological implications, compares existing literature, and addresses long-term follow-up considerations. This case underscores the clinical and academic importance of individualized evaluation and tailored intervention for exceedingly rare multisystem congenital malformations.